From Instruction to Consultative: Reposition of Pesantren in the Collaboration of Religious Radicalization Policy in Indonesia - Mukhlis, Maulana; Makhya, Syarief (SCAD Independent, 2021)
This study examined the urgency of the reconstruction of the Pondok pesantren position in the religious de-radicalization policy in Indonesia. Islamic boarding school (henceforth: Pondok Pesantren) yet is only positioned as a subordinate institution or as an object of de-radicalization policy in the collaboration of institutional design. As a result, the relationship model that is built is the instructive pattern from the government to Pondok pesantren. This, factually, does not contribute to the positive effect on the effectiveness of the de-radicalization policy. The question of this research was how the relationship model or ideal position of Pondok pesantren in the collaboration of institutional design in religious de-radicalization policy? The research data were collected through interviews, documentation, and literature study, which then were analyzed descriptively. This study summed up that the consultative model would guarantee more toward the support of institutional design in the collaboration of religious de-radicalization policy in Indonesia; to protect the unity of the nation on one hand, and optimize the role of Pondok pesantren on the other hand.